2013
DOI: 10.3390/rs5115926
|View full text |Cite
|
Sign up to set email alerts
|

A Production Efficiency Model-Based Method for Satellite Estimates of Corn and Soybean Yields in the Midwestern US

Abstract: Remote sensing techniques that provide synoptic and repetitive observations over large geographic areas have become increasingly important in studying the role of agriculture in global carbon cycles. However, it is still challenging to model crop yields based on remotely sensed data due to the variation in radiation use efficiency (RUE) across crop types and the effects of spatial heterogeneity. In this paper, we propose a production efficiency model-based method to estimate corn and soybean yields with MODera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 57 publications
(89 reference statements)
1
33
0
1
Order By: Relevance
“…On the other hand, some large-scale modeling studies identified overestimations of crop productivity in comparison with statistical inventory data when applying field-derived ε * GPP values (Lobell et al, 2002;Ruimy et al, 1994;Turner et al, 2006). However, two recent studies that incorporate fine-resolution land use maps and coarse-resolution MODIS data recommend applying field-estimated LUE values for large-scale cropland modeling (Bandaru et al, 2013;Xin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some large-scale modeling studies identified overestimations of crop productivity in comparison with statistical inventory data when applying field-derived ε * GPP values (Lobell et al, 2002;Ruimy et al, 1994;Turner et al, 2006). However, two recent studies that incorporate fine-resolution land use maps and coarse-resolution MODIS data recommend applying field-estimated LUE values for large-scale cropland modeling (Bandaru et al, 2013;Xin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Cropping intensity, which we define here as the number of cropping cycles per year, is an important dimension of land use that is strongly influences water demand and agricultural production [18][19][20][21], but has received relatively little attention. In areas, such as Asia, which have limited lands available for arable expansion, crop production is commonly increased by planting crops more than once a year in the same field [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…de Jong et al, 2012). Several agro-ecosystem modeling applications fall into these categories, including agro-climate forecasting (Funk and Brown, 2006), drought monitoring (Karnieli et al, 2006), and crop yield estimation (Xin et al, 2013). Although NDVI is widely used, it is sensitive to atmospheric effects, soil background, and saturates at high LAI.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%